2021
DOI: 10.1007/s00432-021-03680-w
|View full text |Cite
|
Sign up to set email alerts
|

3D mixed-reality visualization of medical imaging data as a supporting tool for innovative, minimally invasive surgery for gastrointestinal tumors and systemic treatment as a new path in personalized treatment of advanced cancer diseases

Abstract: Background The purpose of this study was to investigate the potential of a combination of 3D mixed-reality visualization of medical images using CarnaLife Holo (MedApp, Poland) system as a supporting tool for innovative, minimally invasive surgery/irreversible electroporation—IRA, Nano-Knife), microwave ablation (MWA)/for advanced gastrointestinal tumors. Eight liver and pancreatic tumor treatments were performed. In all of the patients undergoing laparoscopy or open surgery volume and margin wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Within oncological surgery, MR has been applied for preoperative planning of minimally invasive electroporation and microwave ablation for advanced gastrointestinal tumors of hepatic origin. It improved remote and hospital-based analysis of patient-specific anatomy and optimized surgical approach [ 10 ]. MR-guided surgical planning for liver resection refined understanding of hepatic vascular anatomy and tumor location, improving accuracy of resection while preserving a larger residual liver volume [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within oncological surgery, MR has been applied for preoperative planning of minimally invasive electroporation and microwave ablation for advanced gastrointestinal tumors of hepatic origin. It improved remote and hospital-based analysis of patient-specific anatomy and optimized surgical approach [ 10 ]. MR-guided surgical planning for liver resection refined understanding of hepatic vascular anatomy and tumor location, improving accuracy of resection while preserving a larger residual liver volume [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within oncological surgery, one study reported a reduction in operating time by a third and improved perceived surgical precision during minimally invasive resection of gastrointestinal tumors [ 10 ]. Moreover, MR enabled better identification of dissection lines and understanding of vascular anatomy in hepatic surgery, facilitating segmental resection [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wierzbicki et al. performed a series of MR‐guided resections of liver and pancreas tumours, with an average operative duration of 62.5 ± 21.2 min and inpatient stay of 5.5 ± 1.5 days, and no reported complications 74 …”
Section: Resultsmentioning
confidence: 99%
“…performed a series of MR-guided resections of liver and pancreas tumours, with an average operative duration of 62.5 � 21.2 min and inpatient stay of 5.5 � 1.5 days, and no reported complications. 74 Tang et al reported a case of AR-guided open hilar cholangiocarcinoma resection with left hepatectomy, following which the patient was without complications. 75…”
Section: Open Surgerymentioning
confidence: 99%
“…Most of the studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ] in this review are focused on application of HoloLens 2 in surgical navigation in the operating room and in the emergency department. The use of the AR/MR based system in this context provided the user with computer-generated information superimposed to real-world environment and improved accuracy, safety and efficacy of surgical procedures [ 86 ].…”
Section: Ms Hololens 2 Applications In Medical and Healthcare Context...mentioning
confidence: 99%